Adsorption Isotherms of Benzene and Its Derivatives by RPLC Frontal Analysis - WAN, XIAOLONG; CHOI, DAE-KI; HO ROW, KYUNG (Asian Journal of Chemistry, 2010)
The adsorption behaviour of solute is one of the most importantfactors to design a batch and a continuous liquid chromatographic separationprocess. In liquid chromatography, these behaviours are basedon the adsorption equilibrium between a liquid mobile-phase and a solidstationary-phase. However, almost of the retention models were developedunder linear adsorption isotherm only few researchers have investigatedthe relationship between the adsorption parameters and the mobile phasecomposition and some empirical models were introduced. In this work,the adsorption isotherms were obtained by the frontal analysis for 4low-molecular compounds (benzene, toluene, chlorobenzene and 1,2-dichlorobenzene) on a commercial C18 bonded column. The absorptionbased on the linear and Langmuir models was investigated according tothe changes of the composition of methanol high-enriched eluent. Thecalculations and analysis of the coefficients obtained for both modelsconfirm that the adsorption data for solutes are best modeled with thelinear approach. Langmuir isotherm model couldn't satisfactorilydescribe mechanism and provide the objective information on the physicalnature of the absorption in spite of the acceptable accuracy.